Executive decision - Warner Bros.; Silver Pictures production (Burbank, CA : Warner Home Video, 1996)
A team must board a hijacked 747 in mid-air, disable a nerve-toxin bomb that could kill the U.S. eastern seaboard, and rescue the passengers
Title from container
Director, Stuart Baird; writers, Jim Thomas, John Thomas; producer, Joel Silver
Cast: Kurt Russell, Halle Berry, John Leguizamo, Oliver Platt, Joe Morton, David Suchet, Steven Segal
Keywords: Adventure films; Films for the hearing impaired; Feature films